Fiscal Consolidation and the Cost of Credit : Evidence from Syndicated Loans - Agca, Senay; Igan, Deniz (Washington, D.C. : International Monetary Fund, 2013)
We examine how the cost of corporate credit varies around fiscal consolidations aimed at reducing government debt. Using a new dataset on fiscal consolidations and syndicated corporate loan data, we find that loan spreads increase with fiscal consolidations, especially for small firms, domestic firms, and for firms with limited alternative financing sources. These adverse effects are mitigated substantially if consolidations are large, and can be avoided if consolidations are also accompanied with more adaptable macroeconomic policies and implemented by a stable government. These findings suggest that lenders price the short-term recessionary effects in loans but large consolidations can reduce or undo the increase in spreads, especially under favorable country conditions, by signaling credibility and creating expansionary expectations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet